Transnational civil society an introduction - Batliwala, Srilatha; Brown, Lloyd David 1941- (Kumarian Press, 2006)
"Contains an introduction to the history, achievements, and challenges of transnational civil society initiatives on several critical issues and the forces that catalyzed and shaped those initiatives"--Provided by publisher.